Eosinophilic Gastritis in a Patient Previously Treated with Dupilumab - Masaya Iwamuro; Toshi Murakami; Takehiro Tanaka; Shohei Oka; Seiji Kawano; Yoshiro Kawahara; Hiroyuki Okada (Case Reports in Gastrointestinal Medicine)
A 77-year-old Japanese man with bronchial asthma was treated with dupilumab. Dupilumab treatment was discontinued at the patient’s request after two injections separated by a 2-week interval. The blood eosinophil count was elevated, and an esophagogastroduodenoscopy performed 3 months after dupilumab treatment revealed gastric ulcers; subsequently, eosinophilic gastritis was diagnosed from biopsy examinations. The gastric lesions were resolved by steroid administration. This case report underscores that eosinophil-associated gastrointestinal diseases should be considered in the differential diagnosis of gastric lesions occurring in patients who were treated with dupilumab.